Research Progress on Platinum-Based Antitumor Drugs - Xiao, Ran (Exploring Science Academic Conference Series, 2026)
Cancer is a prevalent disease characterized by uncontrolled proliferation and differentiation of abnormal cells and the ability to metastasize. The treatment and prevention of cancer have become critical tasks for humanity. Platinum -based drugs are metal complexes containing platinum elements that exhibit antitumor activity and are widely used in clinical therapy. The mechanism of action of platinum (IV) antitumor agents involves inducing DNA damage, arresting the cell cycle, thereby promoting apoptosis of cancer cells and reducing mitochondrial membrane potential. Among them, lipophilicity –hydrophilicity partition -tuned platinum (IV) drugs are mainly used in chemotherapy; DNA -targeted platinum drugs are widely applied in chemotherapy, although they are associated with higher toxicity and drug resistance; mitochondria -targeted platinum drugs are formed by introducing mitochondria -targeting bioactive small molecules into platinum (IV), which not only exert antitumor effects but also show antibacterial activity, repair mitochondrial function, and reduce drug resistance; photodynamic platinum (IV) drugs are characterized by low toxicity, high efficiency, and strong targeting ability. Platinum (IV) complexes remain stable under physiological pH conditions and can maintain biological activity under the action of strong reducing agents. Altho ugh photodynamic platinum (IV) drugs exhibit advantages such as low toxicity, high efficacy, and strong targeting, they still face many challenges. The combination of platinum -based antitumor drugs with baicalein can exert multiple biological activities, not only enhancing antitumor efficacy but also offering higher safety and lower toxicity due to the natural origin of baicalein. Combination therapy of platinum -based drugs with other agents is more effective and safer than monotherapy. However, platinum -based drugs are prone to adverse reactions, including nephrotoxicity.